2015
DOI: 10.1038/ngeo2516
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon storage controlled by interactions between geochemistry and climate

Abstract: Artículo de publicación ISISoils are an important site of carbon storage(1). Climate is generally regarded as one of the primary controls over soil organic carbon(1,2), but there is still uncertainty about the direction and magnitude of carbon responses to climate change. Here we show that geochemistry, too, is an important controlling factor for soil carbon storage. We measured a range of soil and climate variables at 24 sites along a 4,000-km-long north-south transect of natural grassland and shrubland in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
421
2
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 615 publications
(446 citation statements)
references
References 24 publications
19
421
2
4
Order By: Relevance
“…) Carr] and western hemlock of western Washington and Oregon. Doetterl, et al (2015) suggested that the interaction between climate and geochemical (pedogenic) factors controlled SOC storage and turnover. In our study, SOC was found to be associated with the silt and clay fraction, similar to the findings of Kalbitz and Kaiser (2007).…”
Section: Disturbance Legacies On Soc Stocksmentioning
confidence: 99%
See 2 more Smart Citations
“…) Carr] and western hemlock of western Washington and Oregon. Doetterl, et al (2015) suggested that the interaction between climate and geochemical (pedogenic) factors controlled SOC storage and turnover. In our study, SOC was found to be associated with the silt and clay fraction, similar to the findings of Kalbitz and Kaiser (2007).…”
Section: Disturbance Legacies On Soc Stocksmentioning
confidence: 99%
“…The particular combination of climatic, ecological and pedological factors of these forests is of major advantage in the context of climate change (Black et al, 2008). Although it has been recognized that soils play a critical role in carbon storage (Doetterl et al, 2015) and that coastal temperate forests have considerable potential to sequester SOC (Carpenter et al, 2014), studies related to SOC stocks and stability are scarce in these ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of soil mineral phase in SOC stabilization (Doetterl et al 2015), further studies should be carried out to examine the relationship between SOC and mineral phase in our future works.…”
Section: Soc and Its Fractionsmentioning
confidence: 99%
“…Indeed, the formation of organo-mineral complexes is evolving as a more important mechanism of soil C stabilization (Mikutta et al, 2006;Marschner et al, 2008;Doetterl et al, 2015). The incorporation of residue-derived C (Table 2) and N (Table 3) in the humin fraction in a relatively short period (240 days) may be evidence of rapid modifications in this previously considered refractory fraction.…”
mentioning
confidence: 99%